Howdie-skelp - Muldoon, Paul 1951- (Farrar, Straus and Giroux, 2021)
"The Pulitzer Prize-winning poet delivers a sharp wake-up call with his fourteenth collection of poetry"--
Keywords: English poetry / Irish authors / 20th century; Poésie anglaise / Auteurs irlandais / 20e siècle; English poetry / Irish authors; 1900-1999; Poetry; poetry; Poésie; Anthologie